SCREENING OF FOUR INDIAN MEDICINAL PLANTS FOR SCREENING OF FOUR INDIAN MEDICINAL PLANTS FOR SCREENING OF FOUR INDIAN MEDICINAL PLANTS FOR IN VITRO ANTIMYCOBACTERIAL ACTIVITY - K. G. PURUSHOTHAM; P. ARUN; J. JOHNSY JAYARANI; R. VASANTHA KUMARI (The Bioscan, 2010)
In the present study an attempt has been made to find out the in vitro antimycobacterial potential of four medicinal plants which, are commonly used to treat respiratory disease in the indigenous systems of medicine. The leaves of Adhatoda vasica, leaves of Aegle marmelos, whole plant of Solanum trilobatum, leaves of Tectona grandis were tested. It was found that, the methanolic extracts of Leaves of Tectona grandis possessed high antimycobacterial activity at a concentration of 200 µg/mL onwards. Whereas the other plants did not inhibit the growth of Mycobacterium tuberculosis even at a concentration of 3200 µg/mL when tested in vitro.